Using of Chemical single fractionation Technique for the detection of heavy metals contaminated Soils shore of the Daghara River / AL-Diwaniyah / Iraq. - Amaar Karem Leelo AL-obaidy, Haider; Aziz Hamza AL-Robai, Hazim (Al-Qadisiyah Journal of Pure Science, 2018)
Three heavy metals (Cd, pb, Cu) deteraionated in the soils of (Daghara River) by using Modifier single chemical fractionation Technique for five chemical phases of heavy metals in samples of studied soils.(available ,carbonate ,oxides and organic matter, residual and total).Cadmium ions in available ,carbonate and oxides and organic matter were with unpolluted level ,while the residual and total phases were with polluted level. Lead and copper ions in available phase ,carbonate and oxides and organic matter ,residual and total phases ,were with unpolluted levels. Generally : We conclude the Modified single chemical fractionation Technique showed high efficiency to determine the polluted levels with studied heavy metals.